Une idée de sacerdoce féminin entre xixe et xxe siècle : les Filles du Cœur de Jésus et la dévotion à la « Vierge Prêtre » - Liviana Gazzetta (Chrétiens et Sociétés, 2019)
The devotion to « Virgo sacerdos », which appealed to the grace of the Virgin Mary as priest (and which was spread in Belgium, France and Italy in the last decades of the nineteenth century and early twentieth century), introduced a first alarm in the Catholic Church for female desire of priesthood. This devotion was developed in particular in the congregation of the Daughters of the Sacred Heart, founded in 1872 by Mary Martiny-Deluil and approved in 1902 by pope Leo XIII. It was a form of spirituality and religious practices related on the idea of the sacerdotal mediation performed by Virgin Mary in the order of Salvation : an idea widely attested in theological research during the Medieval and Modern Age, wich now included a strong demand of reparation for the clergy’s sins. In parallel to the traditional interpretation, this devotion could accredit a sort of Marian way to women priests and for this reason was condemned by three interventions of the Holy Office (1913, 1916, 1927) : so even the use of the title « Virgo sacerdos » has been canceled, not by chance recently rediscovered in an environment of Chatholic feminism.